PENERAPAN KONSEP DIGITAL MARKETING PRODUKSI KREATIF DARI GIRILOYO YANG DIIMPLEMENTASIKAN KE BATIK OASE GALLERY DI BENGKULU - Puspita, Veny; Jonathan Sitompul; Clara Dwi Azhari; Tantio Hasrap; Adelia , Adelia; Al fikra (Jurnal Pengabdian, 2025)
This community service program aims to implement the digital marketing concept that has been successfully applied in Kampung Batik Giriloyo, Yogyakarta, to Batik Oase Gallery in Bengkulu. This strategy was carried out to increase competitiveness, expand markets, and strengthen the digital identity of local batik MSMEs. The method used is Participatory Action Research (PAR), involving 27 MSME participants in training and mentoring over three months. The results showed significant improvements in four key aspects of digital marketing: content, context, community, and connection. Batik Oase Gallery successfully developed more engaging visual content and narratives, built active digital communities, and utilized various digital channels to expand its market reach. Program evaluations showed that most participants experienced improvements in digital visibility, human resource capacity, product innovation, educational tourism appeal, and partnerships. Overall, this activity had a positive impact on the development of the local culture-based creative industry in Bengkulu.